Modelling hydrolysis: Simultaneous versus sequential biodegradation of the hydrolysable fractions. (1st January 2020) - Jimenez, Julie; Charnier, Cyrille; Kouas, Mokhles; Latrille, Eric; Torrijos, Michel; Harmand, Jérôme; Patureau, Dominique; Spérandio, Mathieu; Morgenroth, Eberhard; Béline, Fabrice; Ekama, George; Vanrolleghem, Peter A.; et al.
Highlights: Classical hydrolysis modelling by simultaneous approach was challenged. Accessibility fractionation revealed sequential hydrolysis. ADM1 model was modified and a switching function was introduced. Sequential model fits better than simultaneous model in all the studied cases. Abstract: Hydrolysis is considered the limiting step during solid waste anaerobic digestion (including co-digestion of sludge and biosolids). Mechanisms of hydrolysis are mechanistically not well understood with detrimental impact on model predictive capability. The common approach to multiple substrates is to consider simultaneous degradation of the substrates. This may not have the capacity to separate the different kinetics. Sequential degradation of substrates is theoretically supported by microbial capacity and the composite nature of substrates (bioaccessibility concept). However, this has not been experimentally assessed. Sequential chemical fractionation has been successfully used to define inputs for an anaerobic digestion model. In this paper, sequential extractions of organic substrates were evaluated in order to compare both models. By removing each fraction (from the most accessible to the least accessible fraction) from three different substrates, anaerobic incubation tests showed that for physically structured substrates, such as activated sludge and wheat straw, sequential approach could better describe experimental results, while this was less important for homogeneous materials such as pulped fruit. Following this, anaerobic incubation tests were performed on five substrates. Cumulative methane production was modelled by the simultaneous and sequential approaches. Results showed that the sequential model could fit the experimental data for all the substrates whereas simultaneous model did not work for some substrates.